Gender Designs IT Construction and Deconstruction of Information Society Technology - Zorn, Isabel; Maass, Susanne; Rommes, Els; Schirmer, Carola; Schelhowe, Heidi (Studien Interdisziplinäre Geschlechterforschung, 2007)
How can information technology (IT) paradigms and design processes be studied from a gender perspective? What does IT design look like when its construction is informed by gender research? Though gender research and computing science seem like two separate worlds, this book proves how inspirational a confrontation and combination of those worlds can be. A deconstructive analysis of advanced fields of computing shows the multiple ways in which software design is gendered and how gendering effects are produced by its use. Concepts and assumptions underlying research and development, along with design tools and IT products, teaching methods and materials are studied. The book not only offers a gender analysis of information society technologies, it also shows practical examples of how IT can be different. A gender perspective on IT design can serve as an eye-opener for what tends to be overlooked and left out. It yields innovative ideas and high quality software systems that may empower a large diversity of users for an active participation in our information society.